Tracking cell motion using GM-PHD - Juang, R.R.; Levchenko, A.; Burlina, P. (2009 IEEE International Symposium on Biomedical Imaging: From Nano to Macro, 2009)
We present a method for tracking the movement of multiple cells and their lineage. We use the Gaussian Mixture Probability Hypothesis Density (GM-PHD) filter, a multi-target tracking algorithm, to track the motion of multiple cells over time and to keep track of the lineage of cells as they spawn. We describe a spawning model for the GM-PHD filter as well as modifications to the original GM-PHD algorithm to track lineage. Experimental results are provided illustrating the approach for dense cell colonies.